2013
DOI: 10.1161/atvbaha.113.301593
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Concentration in Subclinical Carotid Atherosclerosis

Abstract: he role of vitamin D, most often measured as circulating 25-hydroxyvitamin D (25(OH)D), also designated calcidiol), in cardiovascular disease (CVD) remains much debated. Whereas the strongest support for the notion that low vitamin D levels promote CVD comes from some prospective studies of incident cardiovascular events or CVD mortality, [1][2][3] other prospective studies of the relationship between the circulating 25(OH)D concentration and risk of CVD have provided discrepant results. [4][5][6] Similarly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…32,33 Our prospective study, however, did not find an association of 25OHD with progression of coronary artery stenosis measured as DS and MLD. In addition to our study, three recent studies showed no association between vitamin D status and progression of carotid intima-media thickness or plaque burden [34][35][36] and three studies did not find any association with coronary artery calcification by computed tomography. [36][37][38] The conflicting findings from cross-sectional and prospective studies may be due to treatment and changes in lifestyle, as cardiovascular events or hospital visits can alter medical treatment and be incentives for diet and lifestyle changes.…”
Section: Discussionsupporting
confidence: 58%
“…32,33 Our prospective study, however, did not find an association of 25OHD with progression of coronary artery stenosis measured as DS and MLD. In addition to our study, three recent studies showed no association between vitamin D status and progression of carotid intima-media thickness or plaque burden [34][35][36] and three studies did not find any association with coronary artery calcification by computed tomography. [36][37][38] The conflicting findings from cross-sectional and prospective studies may be due to treatment and changes in lifestyle, as cardiovascular events or hospital visits can alter medical treatment and be incentives for diet and lifestyle changes.…”
Section: Discussionsupporting
confidence: 58%
“…The 2013 study by Deleskog and colleagues [53] had mixed results. The researchers performed a cross-sectional study with 3430 participants, 8% of whom had deficient serum 25(OH)D levels defined as <51 nmol/L (<20 ng/mL), 82% had insufficient levels defined as 51–75 nmol/L (20–30 ng/mL) and 10% had sufficient levels defined as ˃75 nmol/L (˃30 ng/mL).…”
Section: Findings: Evaluation Using Hill’s Criteria For Causalitymentioning
confidence: 99%
“…Although several previous studies have presented inconsistent finding,[15383940] two other cross-sectional studies observed an inverse relationship between serum 25(OH)D level and arterial stiffness. [1532] In the Framingham offspring study as well, vitamin D deficiency was found to be associated with an increased incidence of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[1532] In the Framingham offspring study as well, vitamin D deficiency was found to be associated with an increased incidence of cardiovascular diseases. [41] Several studies have observed a successful decrease in baPWV prior to supplementation with vitamin D.[2627282930] However, a European cross-sectional study [40] as well as a cross-sectional analysis of the Korean Longitudinal Study on Health and Aging (KLoSHA) [39] showed no association between serum concentration of 25(OH)D and baPWV.…”
Section: Discussionmentioning
confidence: 99%